When Risk is out of Reach: Reconstructing Remediation Processes in Contaminated Sites Management as Deciding under Ignorance - Gross, Matthias (Águas Subterrâneas, 2011)
Whereas different types of risk assessments are important, real world decision making in processes of restoring contaminated land often necessitates an open acknowledgement that ignorance cannot be avoided. In this presentation a sociological reconstruction of different examples of real world decision making is offered to discuss some of the strategies used to cope with ongoing situations involving ignorance in the remediation of areas containing multiple contaminant sources. Analysis of these processes of dealing with the unknown indicates that planning and policy making benefit when limits to knowledge are openly acknowledged and communicated and when scientific‐technical risk assessments are calibrated with these limits in mind. If ignorance is taken as unavoidable, the allocation of blame radically changes its meaning. Such processes can be seen as a lynchpin of successful planning and acting in face of unknowns during remediation processes on contaminated land.